Governance and Compliance in PIA: A Risk-Based Framework for Achieving Financial Sustainability - Khan, Mian Muhammad Ajmal; Ahmed Mehmood Qureshi; Tooba Zaheer (Asosiasi Ahli Administrasi Indonesia, 2025)
Pakistan International Airlines (PIA), founded in 1955, once symbolized national pride and success. However, after experiencing years of prosperity, it has unfortunately descended into one of Pakistan's most financially struggling enterprises, facing immense losses. This study explores the challenges that have led to the decline of Pakistan International Airlines (PIA), once a leading state-owned enterprise, focusing on management, financial oversight, and compliance issues. By applying Governance and Management theories, the research reveals how the lack of proper governance has deeply affected PIA’s economic health and day-to-day operations. Through mixed methods, quantitative data analysis, and comparative studies of PIA's financial performance from 2013 to 2023, the study highlights concerning patterns such as persistent losses, unpredictable revenue growth, and an unsustainable debt ratio. It finds that political influence, poor leadership appointments, and the absence of strong GRC processes have all played a significant role in PIA’s struggles and damaged its international standing, particularly after the 2020 fake pilot license scandal. In contrast, Emirates and Turkish Airlines have thrived globally by integrating effective ESG and GRC strategies into their operations. The findings emphasize that for PIA to regain its financial stability, comply with international standards, and compete on the global stage, comprehensive improvements in governance are necessary. This includes prioritizing professionalism, listening to stakeholders, strengthening risk management practices, and embracing ESG principles to foster long-term success.